Video-capillaroscopy, a promising tool for the clinical evaluation of patients with chronic venous insufficiency - Carpentier, Patrick H.; Trolliet, Corine; Cornu-Thénard, André; Chamberod, Rémy; Laurès, Jérôme; Noilhetas, Janick; Chauvin, Eric (Frontiers in Medicine, 2023)
Background The cutaneous microangiopathy plays a key role in the development of the skin clinical lesions of venous insufficiency. Capillaroscopy allows a non-invasive observation of the superficial skin capillaries of the lower leg, which have previously been shown to be altered in patients with advanced venous disease. As it is now available in a friendly, easy to handle way through modern video devices, we report our findings in a short series of patients with C3–C5 chronic venous disorders using this technique. Methods A total of 21 patients with venous insufficiency (C3–C5 on at least one leg) underwent a capillaroscopic examination of both legs and pictures recorded from the sites of the most severe venous skin lesions. This was performed with a CapXview handheld video-capillaroscope (×100 magnification), allowing easy manual measurement of maximum capillary bulk diameter and capillary density. Results Dramatic changes in capillary density, size, and shape were easily observed at the site of the venous skin lesions. A significant negative linear relationship was found between capillary density and the “C” classes (r = −0.45; P < 0.001). A significant negative correlation was also found between capillary density and bulk diameter (r = −0.52; P < 0.001). The area under the ROC curve for the mathematical prediction of venous skin changes by capillary density was 0.842, which shows the strength of the link between the microvascular and the clinical status. Conclusion Video-capillaroscopy allows a direct observation of the cutaneous venous microangiopathy and provides the possibility to measure capillary density which allows its quantification. This simple to use technique shows the potential for a more precise follow-up and treatment evaluation of the cutaneous consequences of venous disease, which remains to be further investigated.